Complexities in care of unsalvageable patients - Goyal, Shikha (Therapeutic Radiology and Oncology, 2019)
Advanced cancer that is unresponsive to curative strategies in the presence of multiple complicating host and patient factors is a complex matter. The treating physician needs to deal with several unique issues relating to the patient’s educational and social background, psychological condition and ethical dilemmas in addition to the management of physical symptoms. In addition, the physician’s own understanding of these complexities with prior experience or training and the willingness to contribute time and attention play a huge role. We discuss the various issues in management of an incurable situation, our shortcomings and possible remedies.